"Virtually mandatory": A survey of how discipline and institutional commitment shape university lecturers' perceptions of technology. (9th May 2013) - Shelton, Chris
Abstract Although there have been many claims that technology might enhance university teaching, there are wide variations in how technology is actually used by lecturers. This paper presents a survey of 795 university lecturers' perceptions of the use of technology in their teaching, showing how their responses were patterned by institutional and subject differences. There were positive attitudes towards technology across institutions and subjects but also large variations between different technologies. Two groups of technology were identified—"core" technologies, such as Powerpoint, that were used frequently, even when lecturers felt that they were not having a positive impact on learning, and "marginal" technologies, such as blogs, that were used much less frequently and only where they fitted the pedagogic approach or context. Rather than there being "leading" universities that were the highest users of all technologies, institutions tended to be heavier users of some technologies than others. Similarly, subjects could be associated with particular technologies rather than being consistent users of technology in general. The study suggests that university technology policy should reflect different disciplines and contexts rather than "one size fits all" directives.